2015
DOI: 10.1021/acs.joc.5b02378
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II)-Catalyzed Annulation of Alkynes with 2-(Cyanomethyl)phenylboronates Leading to 3,4-Disubstituted 2-Naphthalenamines

Abstract: 1,2-Bis(diphenylphosphino)ethane (dppe)-ligated palladium(II) complexes catalyze the annulation of internal alkynes with 2-(cyanomethyl)phenylboronates to provide 3,4-disubstituted-2-naphthalenamines in good yields. The annulation reaction proceeds under mild and neutral conditions and requires methanol as an essential solvent. In addition to symmetrical alkynes, unsymmetrical alkynes substituted by aryl, alkyl, and alkynyl groups participate in the annulation to afford the corresponding 2-naphthalenamines wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 94 publications
(66 reference statements)
0
20
0
Order By: Relevance
“…The reaction with KOH as a base or those in THF/H 2 O and toluene/H 2 O did not give better results than that under the optimized reaction conditions (entries 15–17). The palladium complex Pd(OCOCF 3 ) 2 (dppe) efficiently catalyzed the reaction of 1 a with 2 , giving a high yield of 3 a in MeOH at 65 °C under the conditions reported by Tsukamoto (entry 18), but the reaction was very sluggish with chiral bisphosphine ligands in place of dppe and the enantioselectivity was not high (entries 18–20).…”
Section: Methodsmentioning
confidence: 88%
See 3 more Smart Citations
“…The reaction with KOH as a base or those in THF/H 2 O and toluene/H 2 O did not give better results than that under the optimized reaction conditions (entries 15–17). The palladium complex Pd(OCOCF 3 ) 2 (dppe) efficiently catalyzed the reaction of 1 a with 2 , giving a high yield of 3 a in MeOH at 65 °C under the conditions reported by Tsukamoto (entry 18), but the reaction was very sluggish with chiral bisphosphine ligands in place of dppe and the enantioselectivity was not high (entries 18–20).…”
Section: Methodsmentioning
confidence: 88%
“…Recently Tsukamoto reported that the palladium complex Pd(OCOCF 3 )(dppe) catalyzes the reaction of internal alkynes with 2‐(cyanomethyl)phenylboronate to give 3,4‐disubstituted 2‐aminonaphthalenes (Scheme b). This report inspired us to apply this annulation reaction to asymmetric synthesis of axially chiral biaryls.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…also took place successfully to provide 2-naphthols 138 or 2-naphthylamines 140, respectively. 53,54 Stoichiometric reactions revealed that the use of methanol as a solvent was effective for both transmetalation and catalyst regeneration.…”
Section: Account Syn Lettmentioning
confidence: 99%